Relations between soil and phytophysiognomies in natural forests - Dick, Grasiele; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
This literature review aims to address the main aspects related to soils and their relation to forest ecosystems, and the contextualization of the edaphic component, in the physical, chemical and biological context, and to identify the results obtained in various studies in this context. The soil that occurs in forests, presents chemical and physical characteristics different from other environments where the maintenance of fertility will occur mainly as a function of nutrient cycling. According to the level of fertility of the soil, physical, biological and even topography and moisture regime conditions, it can be seen that there is greater expression of species or even a predominant forest type. However, these relations are narrow and more pronounced at the level of micro scale influenced significantly by various abiotic factors. So it is essential to include the maximum possible environmental variables to be analyzed when the scope and examine relationships between the type soil and vegetation. We emphasize the importance of broader approaches on the subject, with emphasis on biological aspects of soil, often suppressed in scientific approaches and eat the incorporation of new studies.